Conserving Water & Biodiversity: Traditions of Sacred Groves in India - Agarwal, Mala (European Journal of Sustainable Development, 2016)
Sacred groves, a wide spread phenomenon in cultures across the world, are often associated with religion & culture, are instrumental in preserving biodiversity and nature without being questioned. Scattered all over India e.g. scrub forests in the Thar Desert of Rajasthan maintained by the Bishnois, Hariyali in Uttarakhand, Shinpin in Himachal Pradesh and associated with religion they are often sacrosanct. The sacred groves are self sustained ecosystem and conserve the endemic, endangered & threatened species, medicinal plants and wide variety of cultivars. Water and soil conservation is the most well documented ecological service provided by the sacred groves that helps prevent flash floods and ensures supply of water in lean season in the desert of Rajasthan. Encountering threats like fragmentation, urbanization, and overexploitation now they need governmental support to exist e.g. Introduction of the ‘Protected Area Category Community Reserves’ under the Wild Life (Protection) Amendment Act, 2002. Key words-Water conservation, eco-system, bio diversity, sacred groves.